Barriers to exclusive breastfeeding: A cross-sectional study among mothers in Ho Chi Minh City, Vietnam - Nhan Thi Nguyen; Huong Thi Do; Nhu Thi Van Pham (Belitung Raya Foundation, Indonesia, 2021)
Background: Exclusive breastfeeding provides numerous benefits to the health of infants, mothers, economics, and the environment. However, during the exclusive breastfeeding period, the mothers face many barriers. Objective: This study aimed to describe the perceived barrier of breastfeeding and compare its differences among mothers in Vietnam according to demographic and individual characteristics. Methods: A cross-sectional study was conducted among 246 women in Ho Chi Minh City, Vietnam. Data were derived from the original survey using a self-administered questionnaire asking about the barriers of breastfeeding in three aspects: maternal, infant, and socio-environment. Descriptive statistics, Independent t-test, and ANOVA were used to describe the mothers’ characteristics and the breastfeeding barriers. Results: The barrier from the infants was the most noticeable, followed by socio-environment and maternal barriers, respectively. Breastfeeding in public places (M = 2.93, SD = 0.92), baby’s illness (M = 2.74, SD = 0.99), and insufficient milk supply (M = 2.70, SD =0.99) were considered as major barriers to six-month exclusive breastfeeding among mothers in Ho Chi Minh City, Vietnam. Among the age groups, mothers who were more than 35 years old perceived had lower breastfeeding barriers than the younger mothers (F = 3.67, p = 0.03). Conclusion: The investigation of the barriers against exclusive breastfeeding practice can help nurses and midwives develop breastfeeding promotion programs to promote exclusive breastfeeding rate for women in Vietnam.